Caracterização morfo-agronômica, seleção de descritores e associação entre a divergência genética e a heterose em meloeiro - Torres Filho, José (2008)
The objectives of the present work were to characterize melon plant accessions collected in small farms of the Brazilian Northeast, to select traits for the grouping of accessions and cultivars of melon, to investigate the effects of the genotype x environment interaction and the environment on the grouping of accessions and cultivars and to verify the association between genetic divergence and heterosis in melon of the type Honey Dew. Two experiments were carried out to characterize and to form groups of melon accessionscollected in Northeast Brazil and another experiment was conducted to evaluate seven lines of the type Honey Dew and your hybrids. The experiments werelaid out in randomized complete blocks design with two, two and three replications, respectively. Great variation was observed among the melon accessions for all the descriptors, especially in the fruit descriptors. Variation was verified among and within botanical groups, mainly in the group Cantalupensis. Generally speaking, the accessions were prolific and productives, with fruits of intermediate to big size, with lower pulp firmness and content of soluble solids. The descriptors discard was necessary to eliminate the colinearity in the residual variance-covariance matrix. The discard of the descriptors and the grouping of the accessions were dependent of the evaluation conditions, mainly due to the year effects and the interaction accessions x years. The discarded descriptors in the evaluation were: fruit diameter and fruit mass in 2006; fruit lengthwise diameter, fruit mass and production in 2007; and weight of 100 seeds, fruit production and lengthwise diameter in the 2006-2007 joint analysis. The joint analyses, with and without discard, provided similar groupings, allowing the obtaining of five groups and discrimination between accessions and commercial cultivars. The genetic divergence was not correlated with any parameter for all the evaluated traits